Qualitative Risk Analysis for Contents of Dry Toilets Used to Produce Novel Recycling Fertilizers - Ariane Krause; Franziska Häfner; Florian Augustin; Kai M. Udert (Circular Economy and Sustainability, 2021)
Human excreta are a sustainable, economical source of nutrients, and can be used to produce recycling fertilizer for horticulture by collecting and processing the contents of dry toilets. Herein, we discuss the key categories of risk associated with the main groups of materials commonly found in dry toilets. The study was part of the development of a German product standard for marketable and quality-assured recycling fertilizers from human excreta for use in horticulture. Particular attention is paid to ensuring that the fertilizer is epidemiologically and environmentally harmless and that the quality of the recycling fertilizer is adequate in terms of low pollution and nutrient availability. In sum, the risk of transmissible human pathogens lies within the human excreta, particularly feces; plant materials added during composting are of particular phytosanitary relevance; pharmaceutical residues in excrements and chemical additives are potential sources of pollutants; non-biodegradable contaminants can cause pollution and injury; and the horticultural risks involve mainly the ammonia emission potential and in some cases the salinity effects of urine. These risks can be reduced significantly (i) with education of users around proper operation of dry toilets and the consequences of adding inappropriate waste, (ii) with facilitation of proper use with general waste bins and clear instructions, and importantly (iii) by using modern sanitization and cleaning processes and testing for harmful substances under the guidance of local laws and regulations, ensuring safe and high-quality fertilizers. In conclusion, the benefits of using dry toilet contents to produce fertilizers for use in horticulture are unquestionable. Our analysis highlights the need to support recycling optimization and awareness for the purpose of a sustainable circular economy and to minimize the risk of harm to humans and the environment overall.
Keywords: 330; Human excreta; Compost; Urine; Sanitation; Pollutants; Pharmaceuticals; Nutrient cycling